Sosialisasi Pengaruh Gadget di Desa Kare Kecamatan Kare Kabupaten Madiun - Sukadi Sukadi (JURNAL DAYA-MAS, 2019)
The current generation of millenials born between 1980 and 2000 is a generation that has its own characteristics, they were born when digital technology has become known and used by all levels of society. However, the millennial generation tends not to care about the environment or social conditions. They are more preoccupied with digital technology (mostly gadgets) in their hands. To achieve this, to reduce their tendency with digital technology, especially gadgets, socialization of gadget negative effects on adolescents and parents should be held, with the hope that teenagers and parents will be aware of the negative effects of digital technology, especially gadgets, and parents can control their children. their children use gadgets. Dissemination activities were carried out in Kare Village, Kare Subdistrict, Madiun District and the activities were held at the Kare Village Office. From the results of the socialization it is known that the socialization participants can understand the negative effects of gadgets and how to handle children who are addicted to gadgets.